Electrochemical Behavior of Dysprosium in [EMIm]DCA Ionic Liquid Electrolyte - Kyong Mun Choe; Gun-Se Jo; Kum-Hyok Choe; Chol-Su Ri; Hyon-Ho Ju; Pyong-Hun Kim (UPT Laboratorium Terpadu, Universitas Diponegoro, 2026)
The electrochemical behavior of dysprosium (Dy) in 1-ethyl-3-methylimidazolium dicyanamide ([EMIm]DCA) ionic liquid containing DyCl₃ was comprehensively studied using cyclic voltammetry (CV), chronoamperometry (CA), X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDS). Cyclic voltammetric measurements revealed that the reduction of Dy³⁺ ions to metallic Dy is an irreversible process controlled by the diffusion of Dy³⁺ species, with an average charge transfer coefficient of 0.3898. Chronoamperometric data confirmed the one-step multielectron reduction mechanism of Dy³⁺ and the diffusion-controlled nature of the electrode process. The diffusion coefficient of Dy³⁺ calculated from CV measurements was determined to be 2.08 × 10⁻⁷ cm².s⁻¹, which is in good agreement with the value derived from CA curves. XRD analysis confirmed the formation of metallic Dy with a preferential orientation along the (002) crystallographic plane. SEM and EDS observations demonstrated the feasibility of dysprosium electrodeposition in the [EMIm]DCA ionic liquid electrolyte, with the obtained deposits exhibiting a characteristic microgranular morphology. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).